Crop insurance in Karnataka - Kalavakonda, Vijay (Policy research working paper, 2005)
"The authors examine the performance of the crop insurance scheme in Karnataka, a southern state of India and the second driest state in the country. Their analysis highlights weaknesses in product design, implementation challenges, and operational problems. The authors' finding is that the crop insurance scheme in its current form does not achieve its objectives, either explicit (risk management) or implicit (safety net and containment of both the central and state governments' contingent liability). The crop insurance scheme performs poorly both in terms of coverage (number of hectares insured and number of farmers purchasing insurance) and financial performance. The authors provide a framework for designing a crop insurance scheme based on the premise that insurance is a cost effective risk management techniques. They also provide some new ideas and thinking toward both improving the existing crop insurance scheme and exploring alternatives to the current product, based on an area-yield approach. "--World Bank web site